A new Schistura from the Pearl River in Guangxi, China (Teleostei: Nemacheilidae) - Endruweit, Marco (Zootaxa, 2017)
Schistura paraxena, new species, is described from the Pearl River drainage in Laibin, Guangxi Province, China. The new species is easily distinguished from its congeners in having conspicuous peduncular crests along its dorsal and ventral extremities and a plain beige body coloration with crests brownish gray and a pale spot medially at caudal-fin base. Further characters useful to diagnose the species, but not unique to it, are: 8½ branched dorsal-fin rays; 11–12 pectoral-fin and 9 pelvic-fin rays; modally 38 vertebrae; predorsal length 50–52% SL; caudal-peduncle length 17–18% SL (88–92% HL; 5.6–5.8 times SL); lateral line complete; breast naked; predorsal area scaled; and upper lip not notched.